Aspiration thrombectomy with the Penumbra System for patients with stroke and late onset to treatment: a subset analysis of the COMPLETE registry - Hassan, Ameer E.; Fifi, Johanna T.; Zaidat, Osama O. (Frontiers in Neurology, 2023)
The purpose of this study was to report the safety and performance of aspiration thrombectomy with the Penumbra System for patients with acute ischemic stroke (AIS) due to anterior circulation large vessel occlusion (LVO) and late onset to treatment.Methods: This is a retrospective subset analysis of a global prospective multicenter registry (COMPLETE) that enrolled adults with AIS due to LVO and a pre-stroke modified Rankin Scale score (mRS) of 0 or 1 who were treated first-line with aspiration thrombectomy either alone (A Direct Aspiration First Pass Technique [ADAPT]) or in combination with the 3D Revascularization Device (ADAPT + 3D). This subset analysis included all patients in the registry who had anterior circulation LVO, an Alberta Stroke Program Early CT Score of at least 6, and late onset to treatment (>6 hours from stroke onset to puncture).Results: Of the 650 patients in the COMPLETE registry, 167 were included in this subset analysis. The rate of successful revascularization (modified thrombolysis in cerebral infarction score 2b-3 achieved) at the end of the procedure was 83.2%, the rate of good functional outcome (mRS 0-2) at 90 days was 55.4%, and the all-cause mortality rate at 90 days was 14.4%. No device-related serious adverse events (SAEs) occurred. Procedure-related SAEs occurred in 9 patients (5.4%) within 24 hours and in 12 patients (7.2%) overall. The rate of successful revascularization was higher for patients treated first-line with ADAPT (88.0%) than for patients treated first-line with ADAPT + 3D (75.0%; P = 0.035); no significant difference was observed between the ADAPT and ADAPT + 3D groups for any other primary or secondary outcome.For patients with AIS due to anterior circulation LVO and with late onset to treatment, aspiration thrombectomy with the Penumbra System appears to be safe and effective.The rates of good functional outcome and all-cause mortality from this study compared favorably with those rates from the medical management arms of the DAWN and DEFUSE-3 studies.Registration: URL: https://www.clinicaltrials.gov; Unique identifier: NCT03464565.